Analysis of the impact of adherence to guidelines and expert advice in patients with myelodysplastic syndromes - Kasprzak, A. (Ann Hematol, 2020)
The European Leukemia Net (ELN) guidelines for treatment of myelodysplastic syndromes (MDS) connect heterogeneous MDS subgroups with a number of therapeutic options ranging from best supportive care to allogeneic stem cell transplantation (alloSCT). However, it is currently unknown whether adherence to guideline recommendations translates into improved survival. The sizeable database of the Duesseldorf MDS Registry allowed us to address this question. We first performed a retrospective analysis including 1698 patients (cohort 1) to whom we retrospectively applied the ELN guidelines. We compared patients treated according to the guidelines with patients who deviated from it, either because they received a certain treatment though it was not recommended or because they did not receive that treatment despite being eligible. We also performed a prospective study with 381 patients (cohort 2) who were seen in our department and received guideline-based expert advice. Again, we compared the impact of subsequent guideline-adherent versus non-adherent treatment. For the majority of treatment options (best supportive care, lenalidomide, hypomethylating agents, low-dose chemotherapy, and intensive chemotherapy), we found that adherence to the ELN guidelines did not improve survival in cohort 1. The same was true when patient management was prospectively enhanced through guideline-based treatment advice given by MDS experts (cohort 2). The only exceptions were alloSCT and iron chelation (ICT). Patients receiving ICT and alloSCT as recommended fared significantly better than those who were eligible but received other treatment. Our analysis underscores the limited survival impact of most MDS therapies and suggests to pursue alloSCT in all suitable candidates. [Figure: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00277-020-04325-7.